Protozoal populations drive system-wide variation in the rumen microbiome - Carl M. Kobel; Andy Leu; Arturo Vera-Ponce de León; Ove Øyås; Wanxin Lai; Ianina Altshuler; Live H. Hagen; Rasmus D. Wollenberg; Mads T. Søndergaard; Cassie R. Bakshani; William G. T. Willats; Laura Nicoll; et al. (Nature Communications)
Abstract While rapid progress has been made to characterize the bacterial and archaeal populations of the rumen microbiome, insight into how they interact with keystone protozoal species remains elusive. Here, we reveal two distinct system-wide rumen community types (RCT-A and RCT-B) that are not strongly associated with host phenotype nor genotype but instead linked to protozoal community patterns. We leveraged a series of multi-omic datasets to show that the dominant Epidinium spp. in animals with RCT-B employ a plethora of fiber-degrading enzymes that present enriched Prevotella spp. a favorable carbon landscape to forage upon. Conversely, animals with RCT-A, dominated by genera Isotricha and Entodinium, harbor a more even distribution of fiber, protein, and amino acid metabolizers, reflected by higher detection of metabolites from both protozoal and bacterial activity. Our results indicate that microbiome variation across key protozoal and bacterial populations is interlinked, which should act as an important consideration for future development of microbiome-based technologies.